KONDISI BANK BUMN PERIODE SEBELUM DAN SESUDAH PENGUMUMAN PROGRAM PENEMPATAN UANG NEGARA - Bhaktiyana, Arif Kiyat; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze the impact of the State Money Placement Program on company value, stock prices, and stock abnormal returns at state-owned banks, which is based on the various effects of PEN policies on the economy. The method in this study is the Event Study and also performs a T-test to see the differences in the variables before and after the event period. The variables used are firm value from Tobin's Q calculations, daily closing stock prices, and daily stock abnormal returns. This study found that there was an impact of the State Money Placement program on company value, stock prices, and abnormal returns on shares of BUMN Banks. Where the impact resulted in differences in company value and stock prices in the period before and after. However, there is no difference in abnormal returns, this is due to significant daily abnormal returns that recur before the day of the event, which indicates that investors have responded and rated it as a good signal before the day of the event. This investor response was made possible due to the news that has been circulating regarding government policies to overcome the economic crisis due to the Covid-19 pandemic.